Minimally Invasive Abdominal Repair of a Giant Paraesophageal Hiatal Hernia with Occupation of the Right Thorax in a 53-Year-Old Man - Francisco Navarro; Eduardo Pizarro; Marco Ceroni (Case Reports in Surgery)
Paraesophageal giant hiatal hernia is a rare condition associated with serious complications if not treated surgically. There are no reports of the minimally invasive abdominal repair of a giant hiatal hernia of the stomach almost entirely occupying the right thoracic cavity. The most common clinical presentation includes pathological gastroesophageal reflux, dysphagia, chest pain, or respiratory symptoms such as chronic cough or dyspnoea. Chest computed tomography, upper gastrointestinal endoscopy, and high-resolution oesophageal manometry are used to indicate the best treatment. This article reports the minimally invasive abdominal repair of a case of paraesophageal giant hiatal hernia occupying the right thoracic cavity.